2012
DOI: 10.1007/s11033-012-2155-1
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition of Cymbopogon citratus and Eucalyptus citriodora essential oils and their anti-inflammatory and analgesic properties on Wistar rats

Abstract: Cymbopogon citratus and Eucalyptus citriodora are widely used herbs/plants as a source of ethnomedicines in tropical regions of the world. In this work, we studied the anti-inflammatory and gastroprotective effects of C. citratus and E. citriodora essential oils on formol-induced edema, and acetic acid induced abdominal cramps in Wistar rats. To fully understand the chemically induced anti-inflammatory properties of these plants, we first analyzed the chemical composition of the essential oils. A total of 16 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 20 publications
6
57
0
4
Order By: Relevance
“…In agreement with previous findings (Gbenou et al, 2013), the aliphatic terpene aldehyde citronellal was the major component found in the EO of E. citriodora and accounted for 83.8% of the total. Relatively small amounts of other monoterpenoids such as isopulegol (6.9%), citronellol (5.0%) and citronellyl formate (0.8%) were also detected in this EO.…”
Section: Chemical Analysis Of the Eossupporting
confidence: 92%
“…In agreement with previous findings (Gbenou et al, 2013), the aliphatic terpene aldehyde citronellal was the major component found in the EO of E. citriodora and accounted for 83.8% of the total. Relatively small amounts of other monoterpenoids such as isopulegol (6.9%), citronellol (5.0%) and citronellyl formate (0.8%) were also detected in this EO.…”
Section: Chemical Analysis Of the Eossupporting
confidence: 92%
“…In a related study by Gbenou et al [31], C. citratus EO displayed significant dose dependent edema (formol-induced) inhibition effect over time, and a strong analgesic and antipyretic properties similar to that induced by 50mg/kg of acetyl salicylate, further demonstrating its antiinflammatory effect. The mechanisms underlying the antiinflammatory actions of C. citratus extract is posited to include inhibition of a complex immune-inflammatory mechanism and prostaglandin biosynthesis leading to pyrogens and prostaglandins release respectively [31]. These effects are comparable to the effect of salicylate drugs and non-steroidal anti-inflammatory drugs [31,32].…”
Section: Discussionmentioning
confidence: 80%
“…Quanto à composição, os dois métodos apresentaram como constituintes majoritários o neral e o geranial, resultados que coincidem com os relatados por Oliveira (2011) que obteve estes dois constituintes totalizando 73,83% da constituição do óleo essencial de Capim santo, usando o método da hidrodestilação. Já a composição apresentada (32,42% de Neral, 44,69% de Geranial e 10,72% de Mirceno, totalizando 87,83% da composição total) pelo método de extração a vapor se assemelha a relatada por Gbenou (2013), que obteve mirceno (27,83%), neral (19,93%) e geranial (27,04%) totalizando 74,80% da constituição do óleo essencial de C. Citratus, utilizando este mesmo método de extração. Wenqiang (2007) realizou a extração de cravo-da-índia (Eugenia caryophyllata Thunb) por hidrodestilação e arraste a vapor.…”
Section: Resultados E Discussõesunclassified